Optimizing an ethanol-based fixative for enhanced nucleic acid preservation in cervical samples using a central composite design approach - Ghazal Sedaghat Shayegan; Pouya Salehipour; Ali Najafi; Mohammad Hossein Modarressi (PLoS ONE, 2026)
Background To accurately diagnose cervical cancer, high-quality genetic material (DNA and RNA) from clinical samples is crucial. Current preservation methods often have limitations, including poor RNA stability and safety concerns. This study aimed to develop an optimized ethanol-based fixative to preserve DNA and RNA in cervical samples under ambient conditions. Methods HeLa cells were fixed in ethanol-based fixatives containing polyhydric compounds (Sorbitol and polyethylene glycol [PEG]) and chelating agents. We used a central composite design (CCD) approach to evaluate the effects of pH, Sorbitol concentration, and PEG concentration on nucleic acid preservation. DNA and RNA quality were assessed using agarose gel electrophoresis, PCR, and real-time PCR. Cellular morphology was evaluated using Papanicolaou-stained slides. HPV genotyping of clinical samples was conducted using real-time PCR. Results The optimized fixative, developed in this study consisted of 40% ethanol, 4.3% Sorbitol, 1.2% PEG 8000, with a pH of 5.6. This new formula significantly improved DNA and RNA preservation compared to the commercial solution, PreservCyt. DNA showed high integrity and was successfully amplified in PCR test targeting HPV-18 oncogenes. RNA quality was confirmed through clear 28S and 18S rRNA bands and lower threshold cycle (Ct) values in qRT-PCR. HPV genotyping and morphological analysis revealed excellent preservation, enabling both molecular and cytological evaluations. Conclusion The new ethanol-based fixative represents a promising cost-effective and environmentally friendly solution for preserving nucleic acids and cellular morphology in cervical samples. Its good performance under ambient conditions suggests it may serve as an option for Human Papillomavirus (HPV) testing and cervical cancer prevention, particularly in places with limited resources.